The Provision of Medical Assistance to Victims of the Earthquake in Armenia (for the 30th Anniversary of the Tragedy) - S. G. Musselius; V. G. Teryaev; V. I. Potapov; L. N. Zimina (Неотложная медицинская помощь)
Abstract. The article presents the organization of specialized medical care to patients with crush syndrome, acute liver and kidney failure (ALKF), and endotoxic shock, who suffered in the earthquake in Armenia, delivered via air ambulance to N.V. Sklifosovsky Research Institute. In the present report we defined characteristics of medical supplies, qualified and specialized treatment of patients with combined trauma.